The vitality of the English-speaking communities of Quebec: From community decline to revival - Bourhis, Richard Y. (Centre d’études ethniques des universités montréalaises, Université de Montréal, 2008)

Société, langue et santé : les barrières à l'accès aux services de santé pour les communautés francophones minoritaires - Consortium national de formation en santé (2e forum national de recherche sur la santé des communautés francophones en situation minoritaire, 2008)

Rapport de l’évaluation sommative du Projet de formation et de recherche du Consortium national de formation en santé - LeBlanc, Pierre (Conseillers en gestion PRAXIS, 2008)

Language proficiency, gender and self-reported health: An analysis of the first two waves of the longitudinal survey of immigrants to Canada - Pottie, Kevin; Ng, Edward; Spitzer, Denise; Mohammed, Alia; Glazier, Richard (Canadian Journal of Public Health, 2008)
Background Most immigrants to Canada now come from Asia, the Middle East, the Caribbean and Africa, where cultures and languages often differ significantly from the Canadian context. Subgroups of immigrants experience disparities in health. Inability to communicate in an official language in Canada may be a marker of risk for poor health due to both pre- and post-migration factors. We aimed to study the relationship between language proficiency and self-reported health. Methods We conducted a cross-sectional analysis of the first two surveys of the Longitudinal Survey of Immigrants to Canada (2001, 2003), a population-based cohort study of new immigrants to Canada. Specifically, we used logistic regression analyses to examine the relationship between self-reported health and language proficiency by sex, controlling for a range of health determinants at 6 months (wave 1) and 2 years (wave 2) after arrival. Results After controlling for covariates (age, sex, education, region of birth, immigrant class, job satisfaction, access to health care), analysis of the wave 1 survey showed that poor proficiency in English or French is significantly related to the self-reported poor health (OR=2.0, p<0.01). And this relationship was consistent in the wave 2 survey (OR=1.9, p<0.01). We also found that this statistically significant association between poor language proficiency and self-reported health holds only for women (wave 1 survey OR=2.6, p <0.01, wave 2 survey OR=2.2, p<0.01), not for men. Conclusion The association between poor language proficiency and poor self-reported health, and particularly its significantly greater impact on women, has implications for language training, health care and social services, and health information.

The effects of age and culture on subjective well-being: A case study in the Eastern Townships - Stout, Dale; Filion, Emmalie; Chiasson, Myriam; de Man, Anton; Charpentier, Claude; Pope, Megan (Journal of Eastern Townships Studies, 2008)
The present study of diachronous ratings of subjective well-being (SWB) was modeled on research undertaken by Staudinger, Bluck & Herzberg (2003). In addition, we were interested in determining the effects of culture and context (where one lives) on SWB ratings. To gage these effects, we included the factor of mother tongue and altered the Life Satisfaction Questionnaire by adding a question concerning expected well-being in Quebec. We asked 350 Anglophones and Francophones from the Eastern Townships, aged 18 to 95, to rate their SWB in the past, present, future, and future ‘in Quebec’. The results concerning the effects of chronological age on diachronistic SWB ratings followed the patterns of previous research: young people (aged 18–38) rate past SWB lower than present SWB and future SWB much higher; middle-aged people (aged 39–64) rate their SWB the same regardless of time; And the elderly (67–95) rated past SWB higher than the present and their future SWB much lower. There were no differences between Anglophones or Francophones. Further analysis revealed the disturbing finding that the oldest participants rated their current SWB significantly lower than the other two age groups. In the second half of our study we found that by simply asking Francophones and Anglophones to rate their SWB in the future – first unspecified as to location, and then in a future ‘if they stay in Quebec’ – produced different response patterns. Both future SWB ratings were the same for Francophones, indicating that the questions were simply redundant. The Anglophones, on the other hand, rated their future SWB in Quebec consistently lower than an unspecified future.

Access to health care services: East-End Montreal (Quebec) English-speaking elderly experience [master's thesis, McGill University] - Thomas, Rosemary Hellen. (2008)